The Analysis Of Difficulty Learning Chemistry Of Students Class X In Man 2 Palu - Yustika Yani, Dewi; Sabang, Sri Mulyani; Afadil, Afadil; Ahmar, Dwi Satria (Media Eksakta, 2025)
Analysys Of Difficuality Learning Chemistry Of Students In MAN 2 Palu Chemistry Education Study Program, Department of Mathematics and Natural Sciences Education, Faculty of Teacher Training and Education, Tadulako University, Palu. This study aims to determine the types and factors that affect the chemistry learning difficulties of students in class X IPA 5 MAN 2 Palu. This type of research is descriptive research. Collecting data using learning outcomes test instruments consisting of 20 essay questions and a questionnaire consisting of 40 questions, the results showed that students had learning difficulties the average score obtained was 27.4% meaning the criteria were very lacking. Internal Factors causing learning difficulties Attitudes to learning (85.16% of the category are very good), motivation (54.17% of the category is less), interest (69.56% of the good category) and health (85.55% of the category is very good), while external factors of family, school and society with an average percentage of the three indicators are 79.85% (good category).